Pengaruh Peran Perangkat Desa, Transparansi, Dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa (Studiempirispada Pemerintahan Desadikecamatan Sitellutali Urang Jehe Kabupaten Pakpak Bharat) - rosi Magdalena Berutu; azizul kholis; esa setiana (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This research aims to determine the influence of the role of village officials on the accountability of village fund management, the influence of transparency on the accountability of village fund management, the influence of community participation on the accountability of village fund management.The population in this study was all village officials in Sitellu Tali Urang Jehe District, which consists of 10 villages. The sampling technique used saturated sampling with a sample size of 60 respondents. The data collection technique uses a questionnaire distributed to village heads, village secretaries, heads of finance, heads of general affairs, heads of welfare and services, and heads of government. The data analysis techniques used are descriptive statistical analysis, validity and reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing using SPSS 25 software.The research results show that the role of village officials has a positive effect on the accountability of village fund management with a sig-t value of 0.003 < 0.05. Transparency has no effect on Village Fund Management Accountability, with a sig-t value of 0.818 > 0.05. Community participation has a positive effect on Village Fund Management Accountability with a sig-t value of 0.000 < 0.05. The conclusion of this research is that the role of village officials influences the accountability of village fund management, transparency does not influence the accountability of village fund management, community participation influences the accountability of village fund management